Is the Political Business Cycle for Real? - S. Brock Blomberg; Gregory D. Hess (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper constructs and examines a macroeconomic model which combines features from both real and political business cycle models. We augment a standard real business cycle tax model by allowing for varying levels of government partisanship and competence in order to replicate two important empirical regularities: First, that on average the economy expands early under Democratic Presidents and contracts early under Republican Presidents. Second, that Presidents whose parties successfully retain the presidency have stronger than average growth in the second half of their terms. The model generates both of these features that conform to U.S. Post World War II data.
Keywords: 330; Political business cycle